Elias Canetti and the empty ground for right - Punzi, Corrado (Nómadas. Critical Journal of Social and Juridical Sciences, 2015)
Trying to highlight the juridical reflection of a writer like Elias Canetti at the beginning could let puzzled both people who distrust the relationship between literature and law and people who consider Canetti’s academic contribution is exiguous or confined to a psycho- sociological analysis of crowd and power. However, even if Canetti speaks actually seldom about right and let it tacit coincide with power, according to us it is possible to demonstrate as the concept of Law, even if in a twilight zone, permeate the entire Canetti’s narration and constitute the key brick to support and interpret the whole architecture of his thought. In fact, Canetti’s intense keenness on Kafka, allows him to inherit his vision of power and law, but even to elaborate on it.